Causes of Mortality in ICU-Acquired Weakness. (March 2020) - van Wagenberg, Linda; Witteveen, Esther; Wieske, Luuk; Horn, Janneke
Background: Intensive care unit–acquired weakness (ICU-AW) is a common complication of critical illness and is associated with increased mortality, longer mechanical ventilation and longer hospital stay. Little is known about the causes of mortality in patients with ICU-AW. In this study, we aimed to give an overview of the causes of death in a population diagnosed with ICU-AW during hospital admission. Methods: Data from a prospective cohort study in the mixed medical–surgical ICU of the Academic Medical Center in Amsterdam were used. Patients were included when mechanically ventilated for more than 48 hours. Intensive care unit–acquired weakness was defined as a mean medical research council score <4. Baseline data and data on the time of death were collected. Results: Fifty-three patients were included. Irreversible shock with multiple organ failure (MOF) was the most common cause of death (28/53 of patients; 26 patients with septic shock and 2 patients with hypovolemic shock). Most common site of sepsis was abdominal (38.5%) and pulmonary (19.2%). On admission to the ICU, 53% had a do-not-resuscitate code. In 74% of the patients, further treatment limitations were implemented during their ICU stay. Conclusion: In this cohort of patients with ICU-AW, most patients died of irreversible shock with MOF, caused by sepsis.